Recent Advances in NMR: Aggregation, Solvation, and Dynamics of Selected Organolithium Compounds - Oulyadi, Hassan (Synthesis, 2018)
Nuclear magnetic resonance (NMR) spectroscopy is the most widely used analytical technique to study the structure and dynamics of organolithium compounds, which are the most popular reagents in organic synthesis due to their great diversity and high reactivity. The main strength of this method is that it allows direct analysis in solution of the aggregation, dynamic, and solvation state of reactive intermediates. In this review, we present the NMR tools (nD) involving the 6Li isotope and DOSY experiments with internal references and illustrate their contribution in the structural and dynamic characterization of organolithium compounds in solution through some selected example.1 Introduction2 Advantages of the 6Li isotope3 NMR Experiments Involving the 6Li Isotope4 Diffusion Ordered NMR Experiments5 Application of NMR to the Structural Characterization of Organolithium Species6 Conclusion
Keywords: NMR; lithium; DOSY; organolithium; mixed aggregates; lithium phosphido-borane